Chiral Derivatives of Xanthones: Investigation of the Effect of Enantioselectivity on Inhibition of Cyclooxygenases (COX-1 and COX-2) and Binding Interaction with Human Serum Albumin - Carla Fernandes; Andreia Palmeira; Inês I. Ramos; Carlos Carneiro; Carlos Afonso; Maria Elizabeth Tiritan; Honorina Cidade; Paula C.A.G. Pinto; M. Lúcia M.F.S. Saraiva; Salette Reis; Madalena M.M. Pinto (MDPI AG, 2017)
Searching of new enantiomerically pure chiral derivatives of xanthones (CDXs) with potential pharmacological properties, particularly those with anti-inflammatory activity, has remained an area of interest of our group. Herein, we describe in silico studies and in vitro inhibitory assays of cyclooxygenases (COX-1 and COX-2) for different enantiomeric pairs of CDXs. The evaluation of the inhibitory activities was performed by using the COX Inhibitor Screening Assay Kit. Docking simulations between the small molecules (CDXs; known ligands and decoys) and the enzyme targets were undertaken with AutoDock Vina embedded in PyRx-Virtual Screening Tool software. All the CDXs evaluated exhibited COX-1 and COX-2 inhibition potential as predicted. Considering that the (S)-(−)-enantiomer of the nonsteroidal anti-inflammatory drug ketoprofen preferentially binds to albumin, resulting in lower free plasma concentration than (R)-(+)-enantiomer, protein binding affinity for CDXs was also evaluated by spectrofluorimetry as well as in in silico. For some CDXs enantioselectivity was observed.